Horizons of the mind. a tribute to Prakash Panangaden : essays dedicated to Prakash Panangaden on the occasion of His 60th Birthday - Kashefi, Elham; Palamidessi, Catuscia; Rutten, Jan; Breugel, Franck (Lecture Notes in Computer Science, 2014)
This Festschrift volume contains papers presented at a conference, Prakash Fest, held in honor of Prakash Panangaden, in Oxford, UK, in May 2014, to celebrate his 60th birthday. Prakash Panangaden has worked on a large variety of topics including probabilistic and concurrent computation, logics and duality and quantum information and computation. Despite the enormous breadth of his research, he has made significant and deep contributions. For example, he introduced logic and a real-valued interpretation of the logic to capture equivalence of probabilistic processes quantitatively. The 25 papers included in this volume were carefully reviewed. They cover a large variety of topics in theoretical computer science.